Perwujudan Profil Pelajar Pancasila dalam Pendidikan Abad ke-21 - Rekha Indah Sitanggang; Liesna Andriany (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This research aims to find out how the implementation of the Pancasila student profile program has an impact on the formation of student character in 21st century education in Indonesia. The approach used in this study is a qualitative approach. The data collection technique used involves collecting Library document sources. The results of this research show the success of learning the Pancasila student profila which strengthens the character of students in accordance with national education goals. So if the Pancasila syudent profile is optimized in its implementation, the Pancasila character of students will be formed.